2016
DOI: 10.1371/journal.pone.0159847
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Fitness of Influenza B Viruses Possessing E119A and H274Y Neuraminidase Inhibitor Resistance–Associated Substitutions in Ferrets

Abstract: Neuraminidase (NA) inhibitors (NAIs) are the only antiviral drugs recommended for influenza treatment and prophylaxis. Although NAI-resistant influenza B viruses that could pose a threat to public health have been reported in the field, their fitness is poorly understood. We evaluated in ferrets the pathogenicity and relative fitness of reverse genetics (rg)–generated influenza B/Yamanashi/166/1998-like viruses containing E119A or H274Y NA substitutions (N2 numbering). Ferrets inoculated with NAI-susceptible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Furthermore, a recent study found that the proportion of deaths in children hospitalized with influenza attributable to influenza B virus is 1.1%, compared to 0.4% for influenza A virus (14). Finally, oseltamivir treatment seems to be less effective against influenza B viruses than against influenza A viruses (15)(16)(17), and oseltamivir-resistant mutants emerge (18)(19)(20), sometimes without a loss of fitness (21,22). Current influenza virus vaccines are an effective prophylactic countermeasure against influenza B virus infections.…”
mentioning
confidence: 99%
“…Furthermore, a recent study found that the proportion of deaths in children hospitalized with influenza attributable to influenza B virus is 1.1%, compared to 0.4% for influenza A virus (14). Finally, oseltamivir treatment seems to be less effective against influenza B viruses than against influenza A viruses (15)(16)(17), and oseltamivir-resistant mutants emerge (18)(19)(20), sometimes without a loss of fitness (21,22). Current influenza virus vaccines are an effective prophylactic countermeasure against influenza B virus infections.…”
mentioning
confidence: 99%
“…We show that the MUT-Y273 virus had equivalent NA activity and expression to the WT-H273 virus, but delayed growth in cell culture. Previous experiments using a rg-H273Y virus showed that relative to the rg-WT, the rg-H273Y virus had significantly higher NA activity and surface expression, and superior replication kinetics in a competitive mixtures experiment in normal human bronchial epithelial cells (14, 22, 23). The discrepancy in these fitness outcomes between our 2015 H273Y virus and a 1998 rg-H273Y virus may be due to differences in viral background (16 amino acid differences).…”
Section: Discussionmentioning
confidence: 98%
“…A number of different NA substitutions at conserved amino acid positions (e.g. E117, D197, I221 and H273) have previously been described to confer reduced inhibition by the NAIs in vitro (8, 12-21), but the impact of these substitutions on enzyme function, virus replication or transmissibility, has only been assessed in a limited number of studies (14, 22, 23). The fitness of influenza B viruses with either the H273Y or D197N NA substitution is of particular interest as a number of viruses with either substitution have been recently found in patients in community settings who, unlike hospitalized or immunocompromised patients, do not typically receive NAI treatment (8, 9, 17, 18, 24).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Abed et al [12] reported attenuated replication fitness and instability of the E119D mutation variants both in vitro (MDCK and ST6GalI-MDCK) and in vivo (mice and guinea pigs). For other subtypes, mutations at the 119 NA residue, such as E119V of influenza A(H3N2), and E117A of influenza B virus (B numbering is used throughout for influenza B NA residues) have been reported to confer resistance to multiple NAIs and reduce replication fitness in vitro [14][15][16].…”
Section: Selection Of Multi-drug Resistant Influenza a And B Viruses mentioning
confidence: 99%